Iron‐Catalysed Carbene Transfer to Isocyanides as a Platform for Heterocycle Synthesis. Issue 9 (20th December 2022) - Roose, Thomas R.; Preschel, H. Daniel; Mayo Tejedor, Helena; Roozee, Jasper C.; Hamlin, Trevor A.; Maes, Bert U. W.; Ruijter, Eelco; Orru, Romano V. A.
Abstract: An iron‐catalysed carbene transfer reaction of diazo compounds to isocyanides has been developed. The resulting ketenimines are trapped in situ with various bisnucleophiles to access a range of densely functionalized heterocycles (pyrimidinones, dihydropyrazolones, 1 H ‐tetrazoles) in a one‐pot process. The electron‐rich Hieber anion ([Fe(CO)3 NO] − ) facilitates efficient catalytic carbene transfer from acceptor‐type α‐diazo carbonyl compounds to isocyanides, providing a cost‐efficient and benign alternative to similar noble metal‐catalysed processes. Based on DFT calculations a plausible reaction mechanism for activation of the α‐diazo carbonyl carbene precursor and ketenimine formation is provided. Abstract : The readily available low‐valent iron complex [Fe(CO)3 NO] − catalyzes the efficient transfer of carbenes to isocyanides. The resulting ketenimines undergo in situ cyclocondensation with various bisnucleophiles to give a broad range of medicinally relevant heterocycles. A plausible mechanism for the carbene transfer is proposed based on DFT calculations.